Analisis Pemberian Pinjaman Langsung sebagai Upaya untuk Pembiayaan Infrastruktur Transportasi Darat di Indonesia - Xavier Nugraha; Ave Maria Frisa Katherina; Patricia Inge Felany; Faizal Kurniawan (Jurnal Ilmu Hukum, 2021)
In the futuristic era, transportation is one of the essential necessities for society. The dynamism of urban and rural life makes all groups of people need adequate and usable accommodation in general. However, land transportation infrastructure in Indonesia is not maximally available so it requires a lot of development. The construction of transportation infrastructure requires enormous costs, so the solution that can be used is to use a financing scheme. One of the simpler financing schemes is direct lending. The purpose of this research are to explain two main topics. First, is to analyze the legal relation of the parties in providing direct lending to finance transportation infrastructure. Second, is to determine the legal remedies that the government can take when the borrowers default on lending to finance transportation infrastructure. The type of research used is doctrinal legal research so as to produce a clear and detailed legal analysis regarding direct lending to finance land transportation infrastructure. When a borrower, who has been bound in an agreement with a lender, breach of contract, the borrower can be subject to two options of legal remedies.